Pengaruh Growth Opportunity, Leverage, Firm Size dan Profitabilitas Terhadap Cash Holding (Studi Pada Perusahaan Sektor Barang dan Konsumsi yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2020) - Alifia Nur Oktafiana; Solikul Hidayat (Accounting Study Program, Faculty of Economics and Business, 2022)
This study aims to measure and determine the cash holding owned by the company. In addition, it is also to examine and determine the relationship between the effect of growth opportunity, leverage, firm size and profitability on cash holding in goods and consumption sector companies listed on the Indonesia Stock Exchange in 2017-2020. The analytical method used is descriptive statistical analysis, classical assumption test, multiple linear regression analysis and hypothesis testing using the SPSS application. Determination of the sample in this study using purposive sampling technique so that the number of research samples obtained is 68 companies. The results of this study indicate that growth opportunity has a positive significant effect on cash holding. This means that the better the growth opportunity, the more cash holding will increase. Leverage has a negative significant effect on cash holding, meaning that the higher the leverage, the lower the cash holding. Firm size has no effect on cash holding. This means that the size of the company is not able to affect the cash holding. Profitability has a positive significant effect on cash holding. This means that the higher the profitability, the more cash holding will increase.